Perbaikan Saluran Air di Kelurahan Meteseh Kecamatan Tembalang Kota Semarang - Nicky Areta Tiaraningtyas; Nurti Kusuma Anggraini; Diah Rahmawati (Jurnal Pengabdian KOLABORATIF, 2024)
The climate, weather, and rainfall conditions that occur in the Meteseh Village, Tembalang District, Semarang City, especially in the Bukit Kencana Jaya area, are quite high during the rainy season. As a result of housing developments that may not consider the problem of drainage properly, some places experience soil erosion. Based on the results of observations at the location, it was shown that there were several points of the water channel that were damaged. This condition can cause blockage or overflow of water when the intensity of rain increases due to disruption of the water channel. If a puddle occurs, it can become a breeding ground for mosquitoes that have the potential to cause disease. It is necessary to repair the water channel to restore its function of the water channel. The implementation method starts with a field survey, then socializes the repair and maintenance of waterways, and direct practice of repairing damaged waterways. The repair was carried out by replacing the base of the canal using a U-40 cm concrete pipe and plastering on the sides so that the water channel would not experience erosion and could function properly again.